Nonunitary structure of unergative verbs in Georgian - Nash, Léa (Natural language and linguistic theory, 2022)
Traditionally defined as intransitive activity denoting verbs with agent argument, unergative predicates can be structured differently within the same language and cross-linguistically. In some languages, they are straightforwardly represented as monovalent verbs with Agent argument. In others, where agentivity and dyadicity are interdependent, unergatives are subject to argument structure modification. In Georgian, unergatives share ergative case-assigning property with agentive transitives and Viewpoint sensitivity with statives. Both properties are best accounted for if unergatives are underlyingly stative predicates with Holder arguments that undergo causativisation in the perfective. Structuring unergatives in perfective aspect as bivalent reflexive causatives with coindexed Agent and Holder supports the analysis of ergative case along a modified algorithm of dependent case theory: in Georgian, ergative is assigned to the higher argument in a bi-argumental verbal template. Variable behaviour of unergatives with dative arguments calls for further refinement of their structure. While most are underlyingly simplex stative verbs, a class of behaviour-denoting unergatives is structured as complex predicates where a stative light verb combines with a nominal/adjectival predicate. Shaped by general structural constraints, every configurational option proposed in the study yields a predicate with one agentive event participant, in conformity with a traditional definition of unergativity.